Differentiation Strategies for the exporting Hass avocado (Persea Americana Mill) from Agrícola Agrícola Yotita S.A. company to Germany - 2016 - Suárez Mendoza, Gianella Estefany (2017)
This research has as main objective “to propose differentiation strategies to improve the export of Hass avocado from Negociación Agrícola Yotita S.A. Company to Germany 2016. For this reason, it focuses on differentiation strategies of Keller & Kotler, which determine that clients can perceive a company as unique. To obtain the information, three populations have been taken into account: The staff of the Negociación Agrícola Yotita S.A. (object of study); exporting companies of Hass avocado, such as Tropical Farm S.A.C, Consorcio de Frutas Lambayeque S.A.C and Agrícola Cerro Prieto S.A. and the specialists in foreign trade issues: BA. Corvacho Valderrama Paola and Dr. Querevalú Morante Carlos, who were interviewed in detail. According to the results, differentiation strategies constitute an effective way to increase exports, applied in this research on Hass avocado from the Negociación Agrícola Yotita S.A., in the product aspects through the most up-to-date international certification as The GlobalG.A.P. 5.0. Respect to staff, differentiation is achieved through courses or trainings, mainly in Hass avocado crop management. As a third aspect, through the reputation, that is to say that the image of the company is consolidated in the mind of the client through the international fair Fruit Logística in Germany; allowing the optimization of the export of Hass avocado to the German market.